2018
DOI: 10.1038/s41467-018-06152-x
|View full text |Cite
|
Sign up to set email alerts
|

LNMAT1 promotes lymphatic metastasis of bladder cancer via CCL2 dependent macrophage recruitment

Abstract: Tumor-associated macrophages (TAMs) are the most abundant inflammatory infiltrates in the tumor microenvironment and contribute to lymph node (LN) metastasis. However, the precise mechanisms of TAMs-induced LN metastasis remain largely unknown. Herein, we identify a long noncoding RNA, termed Lymph Node Metastasis Associated Transcript 1 (LNMAT1), which is upregulated in LN-positive bladder cancer and associated with LN metastasis and prognosis. Through gain and loss of function approaches, we find that LNMAT1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
268
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 325 publications
(276 citation statements)
references
References 55 publications
7
268
0
1
Order By: Relevance
“…Chen et al reported that lymph node metastasis associated transcript 1 (LNMAT1), a novel lncRNA, was significantly upregulated in bladder cancers with lymph node metastasis. Moreover, enhanced LNMAT1 expression was significantly associated with more advanced clinicopathological characteristics, which indicated a poor survival for patients with bladder cancer (45). LNMAT1 is predominantly localized in the nucleus and recruits hnRNPL to the CCL2 promoter, which results in H3K4 tri-methylation and transcriptional activation (45).…”
Section: Effect Of Lncrna On Immune Cells Within Tmementioning
confidence: 99%
See 2 more Smart Citations
“…Chen et al reported that lymph node metastasis associated transcript 1 (LNMAT1), a novel lncRNA, was significantly upregulated in bladder cancers with lymph node metastasis. Moreover, enhanced LNMAT1 expression was significantly associated with more advanced clinicopathological characteristics, which indicated a poor survival for patients with bladder cancer (45). LNMAT1 is predominantly localized in the nucleus and recruits hnRNPL to the CCL2 promoter, which results in H3K4 tri-methylation and transcriptional activation (45).…”
Section: Effect Of Lncrna On Immune Cells Within Tmementioning
confidence: 99%
“…Moreover, enhanced LNMAT1 expression was significantly associated with more advanced clinicopathological characteristics, which indicated a poor survival for patients with bladder cancer (45). LNMAT1 is predominantly localized in the nucleus and recruits hnRNPL to the CCL2 promoter, which results in H3K4 tri-methylation and transcriptional activation (45). Subsequently, CCL2 activated by LNMAT1 recruits macrophages into the tumor mass and promotes the lymphatic metastasis via VEGF-C excretion (45).…”
Section: Effect Of Lncrna On Immune Cells Within Tmementioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have revealed that cytoplasmic lncRNAs generally function as ceRNAs to regulate mRNA expression via sponging versatile miRNAs, thereby playing a pivotal role in cancer metastasis (Lian et al , ; Shan et al , ; Sun et al , ; Wang and Kong, ; Yan et al , ). In fact, lncRNAs exert their functions in several biological processes via interaction with DNA, proteins, and RNAs, which is dependent on the subcellular localization of the lncRNAs within the cells to a large extent (Chen et al , ). In the current study, using RNA FISH and nuclear–cytoplasmic fractionation assays, we found that PCAT7 can be mainly detected in the cytoplasm of PCa cells, suggesting that PCAT7 may function as a ceRNA in bone metastasis of PCa, which is also supported by previous findings in nasopharyngeal carcinoma and nonsmall cell lung cancer (Liu et al , ; Liu et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Long noncoding RNAs (lncRNAs) are a class of RNA transcripts with no protein‐coding capacity that is greater than 200 nt in length. They regulate many biological processes through various mechanisms, including scaffolds or guides to regulate interactions between proteins and genes, decoys to bind proteins, and enhancers to modulate transcription of their target genes (Chen et al , ). Notably, recent studies have identified that lncRNAs can function as competitive endogenous RNAs (ceRNA) and are able to serve as a ‘miRNA sponge’ to derepress miRNA‐targeted mRNA expression (Karreth et al , ; Tay et al , ).…”
Section: Introductionmentioning
confidence: 99%